Karnataka: Perspective Plan 2001 Volume-II Report of the Expert Group - Planning Commission (Planning Commission, 1989)
We present below a profile of some of the alternative uses to which an input-output table, either in the form of a transaction matrix or as a coefficient matrix could be put. As stated earlier, the coefficients of backward and forward linkages could be worked out for the different sectors - which information could be used for ranking the different sectors in terms of their potential output-inducement effects.
Government of Karnataka